A General and Mild Approach to Controllable Preparation of Manganese‐Based Micro‐ and Nanostructured Bars for High Performance Lithium‐Ion Batteries. Issue 11 (16th February 2016) - Ma, Guo; Li, Sheng; Zhang, Weixin; Yang, Zeheng; Liu, Shulin; Fan, Xiaoming; Chen, Fei; Tian, Yuan; Zhang, Weibo; Yang, Shihe; Li, Mei
Abstract: One‐dimensional (1D) micro‐ and nanostructured electrode materials with controllable phase and composition are appealing materials for use in lithium‐ion batteries with high energy and power densities, but they are challenging to prepare. Herein, a novel ethanol–water mediated co‐precipitation method by a chimie douce route (synthesis conducted under mild conditions) has been exploited to selectively prepare an extensive series of manganese‐based electrode materials, manifesting the considerable generalizability and efficacy of the method. Moreover, by simply tuning the mixed solvent and reagents, transition metal oxide bars with differing aspect ratios and compositions were prepared with an unprecedented uniformity. Application prospects are demonstrated by Li‐rich 0.5 Li2 MnO3 ⋅0.5 LiNi1/3 Co1/3 Mn1/3 O2 bars, which demonstrate excellent reversible capacity and rate capability thanks to the steerable nature of the synthesis and material quality. This work opens a new route to 1D micro‐ and nanostructured materials by customizing the precipitating solvent to orchestrate the crystallization process. Abstract : Above the bar : A general and facile approach was developed for fabrication of 1D micro‐ and nanostructured manganese‐based bars, with applicability to lithium‐ion batteries. Key: 1) solvent effect; 2) nucleation (H2 C2 O4 and H2 O/EtOH added); 3) oriented attachment; 4) Ostwald ripening; 5) calcination; A) precursor; B) product; Mn 2+ (yellow); Ni 2+ (green); Co 2+ (red); Li + (black); MnC2 O4 ▪ (yellow); NiC2 O4 ▪ (green); CoC2 O4 ▪ (red); Li2 C2 O4 ▪ (black).